2022
DOI: 10.1007/s11104-022-05561-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental warming increased greenhouse gas emissions of a near-natural peatland and Sphagnum farming sites

Abstract: Aims Drained peatlands are a major source of greenhouse gases (GHG). Paludiculture is the production of biomass under wet and peat preserving conditions. Despite the growing recognition as GHG mitigation measure, the potential influence of climate warming on paludiculture is still unknown. Methods For two years, we quantified the exchange of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) using manual chambers and surveyed the vegetation compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…Thus, based on the current available data for Zoige peatlands (Table 4), which is supported by that from other observational studies around the world (Andrews et al, 2022;Oestmann et al, 2022), future warming may decrease net C sequestration. In the context of a further 2 C increase (in relation to current temperatures), the Zoige peatland C stock may begin to lose C. However, these estimates are based on limited available data, which does not include the effect of warming on degraded peatlands.…”
Section: Potential Impacts On the Total Zoige Peatland Carbon Stocksupporting
confidence: 77%
“…Thus, based on the current available data for Zoige peatlands (Table 4), which is supported by that from other observational studies around the world (Andrews et al, 2022;Oestmann et al, 2022), future warming may decrease net C sequestration. In the context of a further 2 C increase (in relation to current temperatures), the Zoige peatland C stock may begin to lose C. However, these estimates are based on limited available data, which does not include the effect of warming on degraded peatlands.…”
Section: Potential Impacts On the Total Zoige Peatland Carbon Stocksupporting
confidence: 77%
“…Our results also showed that bryophyte removal increased soil temperature, which may affect soil organic carbon and nitrogen cycling [58,59]. When S. junghuhnianum was removed from the evergreen broad-leaved forest, the surface temperature increased by 1.1 • C. Consequently, this could affect soil organic carbon by altering greenhouse gas emissions and microbial activity in the soil [41]. The Chao1 index in the surface soil decreased, indicating decreased microbial diversity after bryophyte removal.…”
Section: Effect Of Bryophyte Removal On Soil Organic Carbon Stock In ...mentioning
confidence: 54%
“…Understory plant removal affects SOC by decreasing the diversity and function of soil microorganisms [12,38,39]. For example, bryophytes are considered an important driving force in global biogeochemical cycles in terrestrial ecosystems [40,41]. Bryophytes have direct and indirect effects on C cycles through photosynthesis, respiration, and secondary metabolism [42].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature plays an essential role in ecosystem respiration (ER), photosynthesis, as well as net ecosystem CO 2 uptake (Jassey & Signarbieux, 2019; Walker et al., 2016). Generally, warming increases ER due to the stimulation of microbial activities and vegetation growth (Dorrepaal et al., 2009; Lu et al., 2022; Oestmann et al., 2022; Ward et al., 2013), but its impacts on gross primary production (GPP) and net ecosystem CO 2 uptake are uncertain, ranging from decreased to increased fluxes (Helbig et al., 2022; Johnson et al., 2013; Laine et al., 2019; Li et al., 2021; Pearson et al., 2015; Ward et al., 2013). It is yet hard to obtain a general conclusion owing to the limited number of studies.…”
Section: Introductionmentioning
confidence: 99%